Exhibiting Music in a Sound Community - Titon, Jeff (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2015)
Exhibiting music in a sound community announces the presence and potential of an ecological rationality. Two or more beings co-present to each other in sound resonate at the same frequency with one another and comprise a sound community. Co-presence in sound is intersubjective and relational, a subject-to-subject resonant and reciprocal way of knowing, rather than a subject-to-object, asymmetrical and manipulative knowledge. In a sound community music is communicative, as natural as breathing, participatory and exchanged freely, strengthening and sustaining individuals and communities. A sound community exhibits a sound economy, just, participatory and egalitarian. Wealth and power are widely distributed and shared, and maintained through the visible hand of democratic management. A sound economy is based in a sound ecology where exchanges are based in honest signals that invite reciprocity and trust. In a sound ecology, sound being and sound knowing lead to sound action, which is cooperative, mutually beneficial, and just.